Refractory period of single motor nerve fibres in man. Issue 4 (April 1984) - Borg, J
Abstract : Electromyographic single motor unit recordings were used to study the axonal refractory period of 28 accessory nerve innervated motor units in young normal subjects and 10 reinnervated motor units in elderly subjects. The refractory period was measured after a conditioning antidromic propagated nerve impulse and after a conditioning electrical nerve stimulus delivered through the same electrode as the test stimulus. The refractory period after a propagated impulse was 1.83 +/- 0.26 ms when test stimulus strength was 10% above the axonal threshold at rest and 0.88 +/- 0.26 ms when test stimulus strength was 100% above threshold. Corresponding data after an electrical stimulus were 2.38 +/- 0.32 ms and 1.28 +/- 0.22 ms. The difference between the methods was partially due to the effect of stimulus spread when the refractory period was measured after an antidromic propagated nerve impulse. Different properties of the nerve fibre membrane and the surrounding tissues after a propagated nerve impulse and after an electrical stimulus might also contribute. For further studies of motor unit pathology both methods seem equally reliable when proper normal data are available.